Meatiness of tested gilts in three consecutive years - Gogić Marija; Radović Čedomir; Radojković Dragan; Savić Radomir; Petričević Maja; Živković Vladimir; Stojiljković Nenad (Biotechnology in Animal Husbandry, 2019)
In the present study, the aim was to determine the impact of the following factors: age, farm, and gilt genotype, as well as the regression impact of body weight at the end of the performance test on the following tested properties: age at the end of the test/final age (FA), lifetime daily gain (LDG), the backfat thickness measured in two places (according to the Main Breeding program for Central Serbia), the depth of the long back muscle (BM) and the estimated lean meat content/meatiness (M). The study included two farms of pigs (farm 1 and farm 2), for three consecutive years (year 1, year 2 and year 3). The number of tested heads per year was 974 (year 1), 1311 (year 2) and 757 (year 3). The tested gilts were of Swedish Landrace, Large White and Duroc breeds. The gilts originated from 97 sires, while the number of daughters per sires ranged from 10 to 100. The results show that the Duroc animals were the oldest (245 days), which had the highest values for both measures of backfat thickness, but the lowest values for meatiness. In the third study year, the lowest average values were determined for the properties of the LDG, BM and M. The female animals from the farm 1 showed less growth/gain and had lower values for the estimated meatiness. As a result of the study, it was established that all included factors had a very high statistically significant influence on the variation of the tested properties (P <0.001), only the genotype of gilts showed ahigh statistically significant effect on the BM property (P <0.01).